"Should I change myself or not?": Examining (Re)constructed language teacher identity during the COVID-19 pandemic through text-mining. (June 2023) - Zhang, Li; Hwang, Yohan
Abstract: On the basis of interviews with 20 Chinese EFL teachers and text-mining analysis, this study investigates the reconstruction of language teacher identity during the COVID-19 pandemic in terms of context, agency, and practice. The word co-occurrence analysis and collocation statistics with modal verbs coded by KH Coder 3.0 demonstrate that English teachers face two types of identity reconstruction processes: (a) situational context related to various changes and (b) interactional context that causes communication difficulties with students. How teachers enact agency is influenced by their teaching experience. Through practice, teachers reconstruct their identity as solution seekers, positive learners, and confident professionals.